PROSEDUR AUDIT AKUN PIUTANG USAHA PT XYZ OLEH KANTOR AKUNTAN PUBLIK (KAP) REXON NAINGGOLAN DAN REKAN - Eva Della Elsada (2021)
Auditing is an activity of collecting data and evidence by an independent party (an institution that is trusted by the public) regarding the financial statements presented by a company with the aim of providing an assessment/opinion whether the financial statements are reasonable and in accordance with applicable regulations so that the financial statements can be used in making decisions decisions of interested parties. The purpose of the audit of accounts receivable accounts is to ascertain whether the nominal receivables contained in the financial statements are presented fairly according to applicable standards. The discussion is carried out starting from the planning stage of the audit, implementing the accounts receivable audit to the completion of the audit process. Management fulfills responsibilities well from the start of the audit process. Especially in the accounts receivable audit, all data requests submitted by the auditor to management were responded to in a complete and clear manner. The audit procedures performed on the accounts receivable accounts of PT XYZ are in accordance with applicable standards. KAP Rexon Nainggolan and Partners use three procedures in examining accounts receivable accounts of PT XYZ, namely confirmation of accounts receivable, subsequent receipts of accounts receivable accounts and vouching of accounts receivable accounts. After all audit programs and audit procedures were carried out with the result that the presentation of accounts receivable accounts was in accordance with applicable standards and the final remaining nominal balance of trade receivables that did not get evidence was below the PAJE Scope, it can be concluded that the accounts receivable accounts of PT XYZ are presented fairly and not material misstatement.